Rehabilitation of a green sea turtle (Chelonia mydas) after collision with motorboat in the archipelago of Fernando de Noronha, Brazil - da Bôaviagem Freire, Augusto Carlos; Matias de Oliveira, Radan Elvis; de Lorena Pires, Juliana Maia; Fernanda Loffler Niemeyer Attademo; Moreira, Amy Borges; dos Santos Melo, Lucas Inácio; Marques Dantas, Marcus Arthur; Dias de Farias, Daniel Solon; Bomfim, Aline da Costa; Bellini, Claudio; Gavilan, Simone Almeida; de Lima Silva, Flávio José (Brazilian Journal of Case Reports, 2021)
A juvenile green sea turtle (Chelonia mydas) of undetermined sex was rescued on October 16, 2019, in the archipelago of Fernando de Noronha, Pernambuco, Brazil. The animal was presence of active bleeding resulting from two transverse fractures in the carapace, with exposure of the coelomic cavity. Radiological and hematological tests were performed. The animal received therapeutic support and surgical reconstruction of the carapace. The animal was medically cleared and reintroduced into the natural environment 120 days after it was rescued. The protocol used here for both the rehabilitation and the surgical procedure was concluded to be effective.